Comparison between convection and micro wave oven drying of Carica papaya L. peel and characterization of the powdered peel - Manzoor, Sama (2019)
Carica Papaya is a tropical fruit which is widely consumed around the world. The waste by-products produced are underutilized although they show good nutritional properties. Rather than having the waste disposed into the environment, efforts can be made to convert them into value added products by further processing. Thus, this research focuses on producing papaya peel powder, followed by its application in stirred yogurt for the purpose of investigating its effects on yogurt properties. Papaya peel was first dried using a convection oven at 45, 55, and 65 oC and a microwave oven at 250, 440, and 600 W to study its drying kinetics and behaviours. Seven semi-empirical drying models, namely Lewis, Page, Modified Page, Henderson and Pabis, Logarithmic, Two-Term, and Approximation of Diffusion models, were used to fit the drying data obtained. This was followed by characterization of the obtained papaya peel powders, that is, proximate analysis, colour, flow behaviour and antioxidant capacity was investigated. Papaya peel powder was added as a source of dietary fibre to plain stirred yogurt at 0, 1.5 and 3.0% concentration to study its effects on quality properties and sensory profile of yogurt. Results indicated that for oven drying and microwave drying, Page model and Approximation of Diffusion model was the best fit, respectively, with highest coefficient of determination (R²). Effective moisture diffusivity (Deff) was estimated to compare the two drying methods and it was concluded that microwave drying at 600 W exhibited with highest Deff. Additionally, the value of Deff for oven drying and microwave drying was 6.7 x 10-08 to 4.4 x 10-07 and 2.4 x 10-07 to 6.7 x 10-07, respectively. Activation energy was recorded at 61 kJ/mol for oven and 47 W/g for microwave. After drying behaviour was investigated using drying models, characterization of peel powder obtained was done. The powders showed moisture content below 10% and high total dietary fibre content. Colour of each powder sample was analysed which showed that the lightness parameter, L*, reduced as the temperature and power intensity was raised. As per Carr index and Hausner ratio, flowability properties indicated that all the powders had poor to excellent flow. Antioxidant analysis of papaya peel powder was done by DPPH and ABTS assay which showed that all the powders have potential antioxidant properties. After enrichment of stirred yogurt with selected papaya peel powders, quality properties were determined for 21 days storage at 4oC. It was observed that the viscosity values increased during storage while pH values decreased. For colour parameters, it was noted that the values remained generally the same throughout storage. Sensory analysis was conducted for the five stirred yogurt samples prepared at Day 0. Sensory attributes were assessed using nine-point hedonic scale. Stirred yogurt prepared with papaya peel powder dried at 55oC gave the best sensory scores. This research concludes that waste by-products can be utilized after further processing since they are potential sources of nutrients. Application in stirred yogurt is one of the excellent ways of feasible utilization of papaya peels. Additionally, basic foundation for understanding the drying behaviour of papaya peels is provided which can help to choose and design an ideal dryer for papaya peels.